Aldeia indígena Akrãtikatêjê e a castanha-do-pará: levantamento histórico e geográfico para contribuir no processo de certificação indicação geográfica - ALMEIDA, Kleise Oeiras de (2018)
Indigenous people such as the Akrãtikatêjê, Kỳikatêjê and Parkatêjê, located in the mesoregion of the Southeast of Paraense, in the Mãe Maria Indigenous Land, have a direct relationship with forest products, as is the case of Brazil nuts. quite a long time. Even being a factor of conflicts within their territories. The purpose of this is to make a historical and geographic survey of TI Mãe Maria and the Akrãtikatêjê village, Gavião da Montanha village and its relationship with the Brazil nut, aiming to contribute to territorial and environmental management, by conducting a stage for the geographical indication of designation of origin of chestnuts extracted from the forest. In the work interviews were conducted with indigenous Akrãtikatêjê in the village, field research and bibliographical research. The different strategies of resistance and confrontation of policies that harmed its existence in favor of development were verified. A designation of origin for the Brazil nut will be relevant for the Indians, who sell nuts at a price well below the market, for the history and valorization of their territory and products from the forest. The rebirth of a village, through Brazil nut, a source of food and income for indigenous populations, emphasizes the importance of this oilseed as part of the identity of a people.